The Effect of Flipped Classroom Method on Students Writing Skill in Descriptive Text - Firnatha, Disha; Widya Oktarini; Nurkamilah (JELP Journal of English Language and Pedagogy, 2024)
This study is aims to determine the effect of flipped classroom method on students writing skill in descriptive text. The subject of the study was tenth grade of student BDP 1 and BDP 2 of SMK Muhammadiyah 4 Kalisat Jember consisting of 40 students from 2 classes. The results showed that there is a significant difference in writing descriptive text between of students who are taught with a flipped classroom method and those who are taught conventional method. This is based on the results of the mean score from the post-test of the experimental group and the control group. From the post-test it is known that the average value for the experimental group (X BDP 2) is 77.95. The results of the independent t-test have a significance difference of 0.000, which means that there is a significance average difference between the experimental group and the control group. So, it can be stated that the use of flipped classroom method can be an alternative solution to overcome the student’s difficulties in writing a descriptive text.